The Impact of Listening to Quran Recitation during Pain-Inducing Procedure among Patients Receiving Mechanical Ventilation Support: An Interventional Study - Mohammad Rababa; Shatha Al-Sabbah; Audai Hayajneh (Iranian Journal of Nursing and Midwifery Research)
Background: Pain experienced by intubated patients is caused by several extrinsic sources, including nursing care procedures such as endotracheal suctioning. Several nonpharmacological therapies, including listening to Quran recitation, have never been tested for their pain relief effects among intubated patients, despite these therapies being cost-effective, easy to implement, and free of adverse effects. This study aimed to examine the pain-relieving effect of listening to Quran recitation during pain-inducing procedures in patients receiving mechanical ventilation support. Materials and Methods: This pilot study used an experimental design with 32 intubated patients at King Abdullah University Hospital in Irbid, Jordan. The Behavioral Pain Scale and Ramsay Sedation Scale were used to assess pain levels and sedation, and physiologic parameters were monitored before and during endotracheal suctioning. Results: The findings showed significant differences in Behavioral Pain Scale (BPS) scores and heart rate measures between the intervention and control groups after controlling for the level of sedation. The patients in the intervention group scored lower pain and HR measures than those in the control group (F5,26 = 11.47, p < 0.001). Conclusions: The findings showed significant improvement in the levels of pain and heart rate measures among intubated patients who are exposed to Quran recitation. Complementary medicine is essential to the healthcare plans of critically ill patients and their families. Holy Quran recitation has been reported to be a useful nonpharmacological intervention for critically ill Muslim patients.